Student engagement: the key role of Sustainable Transportation at KMUTT Thailand - Kanthamanon, Prasert (Journal of Sustainability Perspectives, 2023)
Abstract. King Mongkut’s University of Technology Thonburi (KMUTT) committed to be Sustainable University for SDGs 2030 since 2017 and   committed to sustainability leadership in all our activities from operations, teaching, to conducting research. Our commitments are to be a sustainable university providing a role model on Energy, Environment, Safety Management Systems and provide sustainability platform to promote sustainability leadership. Sustainable transportation system has been provided by top management policy since 2018 which focus on walk and bike society with zero emission vehicles, free shuttle bus and free bicycle services. In KMUTT, Student engagement is a key role to achieve the sustainable transportation goal which comply to SDG 3: Good Health and Well-being; SDG 7: Affordable and Clean Energy; SDG 11: Sustainable cities and communities and SDG13: Climate Action. KMUTT Green Heart is student’s sustainability leadership team who interested in environmental sustainability which make university and communities surrounded more green and better quality of life and create their own activities to serve sustainable transportation activities for all in KMUTT by using SEP for SDG concept. Moreover, KMUTT initiate sustainable strategy which provide the learning environment to make all campus as living lab, promote people participation and monitoring to make continual improvement with positive reinforcement. The sustainable transportation goal achieved along with the expansion activities to community surround according to the student engagement.Keywords: Sustainable Transportation, Student Engagement, Walk And Bike Society, Zero Emission Vehicles, SDG3, SDG 7, SDG11, SDG 13